Investigation of fatigue performance for new membrane-type LNG CCS at cryogenic temperature. (November 2018) - Oh, Dong-Jin; Kim, Nam-Kyu; Song, Sang-Woo; Kim, Yang-Do; Kim, Myung-Hyun
Abstract: In recent years, various membrane-type liquefied natural gas (LNG) containment systems have been developed to improve the performance related to the insulation system and boil off rate (BOR). In this respect, investigations into the mechanical properties and fatigue strength of the welded joints in a new LNG cargo containment system (CCS) are required to ensure the structural integrity of LNG carriers. In this study, a series of fatigue tests were carried out for five different types of test specimens manufactured using Invar alloy and SUS 304L at ambient and cryogenic temperatures, respectively. It was clearly observed that the fatigue strength at cryogenic temperature is higher than that at ambient temperature. Finally, the FAT value and slope for the welded joints in the new LNG CCS were suggested based on the effective notch stress approach. Highlights: Conducted fatigue strength assessment of welded joint in new membrane-type LNG CCS. Fatigue tests performed at −110 °C and −163 °C to investigate fatigue characteristics under cryogenic environments. Fatigue design curve of new membrane-type LNG CCS is suggested. FAT value for other structural materials can be predicted using their Young's moduli.